2011
DOI: 10.1002/sia.3651
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and migration of phosphorus species within anodic films on an Al‐W alloy

Abstract: The effect of tungsten species on the incorporation and migration of phosphorus species within anodic alumina is investigated. The study employs barrier anodic films, formed on a sputtering-deposited Al-15at.%W alloy in phosphate electrolytes. The films consist of either an outer tungsten-containing region and an inner tungsten-free region, or a tungsten-containing region only. Phosphorus species are shown to migrate inward in the tungsten-containing alumina more slowly than in the tungsten-free alumina. In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The findings are in good agreement with previously reported phosphorus distributions in anodic alumina formed in phosphate electrolytes [11][12][13][14] and show no significant influence of either tungsten or chromium species ͑Table I͒. However, an earlier study found that phosphorus was present only in the outer ϳ0.5 of films formed on an Al-15 atom % W alloy, 20 which suggested a reduced migration rate. Thus, the migration of phosphate ions may be transiently slowed in the present films during their passage through the tungsten-containing region.…”
Section: C439supporting
confidence: 91%
See 1 more Smart Citation
“…The findings are in good agreement with previously reported phosphorus distributions in anodic alumina formed in phosphate electrolytes [11][12][13][14] and show no significant influence of either tungsten or chromium species ͑Table I͒. However, an earlier study found that phosphorus was present only in the outer ϳ0.5 of films formed on an Al-15 atom % W alloy, 20 which suggested a reduced migration rate. Thus, the migration of phosphate ions may be transiently slowed in the present films during their passage through the tungsten-containing region.…”
Section: C439supporting
confidence: 91%
“…Journal of The Electrochemical Society, 157 ͑12͒ C437-C443 ͑2010͒ C438 increases the sputtering rate of anodic alumina. 20 The second peak is due to the phosphorus species incorporated into the residual oxide left by the stripping solution used to flatten the electropolished aluminum. Between the two peaks, the boundary of the film region containing phosphorus species derived from the anodizing electrolyte is evident by a decreasing phosphorus signal.…”
Section: C438mentioning
confidence: 99%
“…The threshold energy, E th , associated with this process can be estimated according to Fowler's law: 28 (I ph ) 0.5 p (hn À E th ) (6) from the long wavelength region of the photocurrent spectra, corresponding to l Z 400 nm, which has been recorded using a 400 nm cut-off filter to avoid the doubling effect (see Fig. 10b).…”
Section: Photoelectrochemical Measurementsmentioning
confidence: 99%
“…However, the film structure and the composition are also dependent upon the electrolyte due to the possible incorporation of foreign species from the anodizing bath. [6][7][8] This is very important if we consider that the presence of foreign species in anodic films could affect the electronic properties of the films with possible detrimental effects on the dielectric properties of the oxides.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that phosphorus extends over about two thirds of the film thickness. Garcia-Vergara and coworkers [ 30 ] also found the phosphorous signal in the anodic alumina film fabricated by anodizing in Na 2 HPO 4 electrolyte. The phosphorous is present from the surface of the film to relative depths of in the range ~0.7 to ~0.8 of the film thickness.…”
Section: Introductionmentioning
confidence: 98%